The nexus of employment and trade : case study of tomato sector in South Africa (1996-2018) - Mokgolobotho, Mpho Stelence (My University, 2024)
Tomato is a significant commodity produced and traded by South Africa. The commodity plays an important role in job creation. South Africa is known as self sufficient producer of fresh tomatoes due to its resource endowments. South Africa exports fresh tomato produce to Botswana, Namibia, Mozambique, and Lesotho. However, unjustified trade bans from neighbouring countries such as Namibia and Botswana threaten jobs in South African agricultural trade. Trade plays a vital role in employment creation and can be captured by the variable which is calculated as domestic employment in gross export. Tomato sector exports contribute to the economy and can enhance foreign exchange rates in the country. The study aims to analyse relationship between domestic employment in gross agricultural exports and tomato sector trade from 1996 to 2018, the study focused on South Africa. The objectives of this study were to establish the causality, long-run and short-run relationship between domestic employment in gross agricultural exports and tomato sector trade in South Africa. Secondary data was employed in this study for tomato imports and exports as well as domestic employment in gross agricultural exports. The objectives were examined using a Vector auto-regressive (VAR) model and Granger causality test. Max-Eigen and trace test from the Johansen co-integration test revealed that domestic employment in gross agricultural exports and tomato sector trade does not have a long-term co-integration. The Granger causality test revealed that domestic employment in gross export in agriculture (EMP) does not cause the amount of tomato exported (export quantity of tomato) (EXPT) in the short term. Furthermore, domestic employment in gross export in agriculture (EMP) does not cause import quantity of tomato (IMPT) in the short run. The study recommends policymakers implement short term policies to address the deviations observed in domestic employment in gross export in agriculture and tomato trade quantities (import quantity and export quantity).
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Granger causality test; VAR model; Tomato sector trade; Gross agricultural exports; Domestic employment; Tomatoes; Tomato industry; Trade adjustment assistance; Foreign trade and employment